Parental Involvement in Public Pre-primary Education in Ilemela District, Tanzania: Factors Influencing Participation - Jenifer Ntabahanyi Samwel; Stellah Jepngetich Keter; Jafari Abdalla (Asian Journal of Education and Social Studies, 2026)
This study explored the factors influencing parental involvement in public pre-primary education in Ilemela District, Mwanza Region, Tanzania. The study was guided by Bronfenbrenner’s Ecological Systems Theory, which explains children’s learning and development through interactions among family, school, community and wider social systems. A qualitative research approach within the interpretivist paradigm was adopted, using a case study design to gain detailed insights into parents’ participation in pre-primary education. The target population comprised 39 public pre-primary schools in Ilemela District Council. Participants included 20 parents of children attending selected public pre-primary schools, 20 teachers and 2 pre-primary education officers. Ten (10) public pre-primary schools were purposively selected, and data were collected through semi-structured interviews and focus group discussions. The data were analysed thematically to identify recurring meanings and patterns related to parental participation in pre-primary education. The findings showed that three interrelated factors influenced parental involvement. First, parents’ awareness of the academic benefits of pre-primary education motivated them to enrol children, monitor attendance and support learning at home. Second, socio-cultural beliefs, community expectations, peer influence and guidance from local educational authorities shaped parents’ decisions to participate in pre-primary education. Third, school-related factors, including a welcoming school environment, teachers’ attitudes, communication practices and supportive parent-teacher relationships, encouraged parents to engage in school activities. The study concluded that individual awareness, social expectations and institutional practices shaped parental involvement in pre-primary education. It recommended strengthening parent-teacher collaboration, enhancing community sensitisation and fostering school environments that promote trust, communication and shared responsibility for children’s early learning.